2022
DOI: 10.1002/mabi.202200103
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Printed Electroactive Hydrogel Architectures with Sub‐100 µm Resolution Promote Myoblast Viability

Abstract: 3D-printed hydrogel scaffolds functionalized with conductive polymers have demonstrated significant potential in regenerative applications for their structural tunability, physiochemical compatibility, and electroactivity. Controllably generating conductive hydrogels with fine features, however, has proven challenging. Here, micro-continuous liquid interface production (𝝁CLIP) method is utilized to 3D print poly(2-hydroxyethyl methacrylate) (pHEMA) hydrogels. With a unique in-situ polymerization approach, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…3D printing has matured into a promising technique for rapidly generating soft matter with complex form factors for biomedical applications, such as stents, scaffolds for tissue regeneration, implants, and soft robotics, among others. [ 42,48,49 ] Printing conductive hydrogels while maintaining structural control of fine (<200 µm) features remains a challenge, [ 42 ] as the incorporation of electroactive fillers into printable resins can dramatically impact the rate of photopolymerization or clog the printing nozzle due to particle aggregation during the printing process—arising from poor particle dispersibility. [ 50 ] Alternatively, 3D printed insulating hydrogels can be endowed with electrical conductivity through 1) soaking the part in monomer solution, and 2) subsequently polymerizing the monomer in situ to generate a double network hydrogel—however such systems have limited control of the final CP loading, and can lack homogenous distribution of incorporated CP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D printing has matured into a promising technique for rapidly generating soft matter with complex form factors for biomedical applications, such as stents, scaffolds for tissue regeneration, implants, and soft robotics, among others. [ 42,48,49 ] Printing conductive hydrogels while maintaining structural control of fine (<200 µm) features remains a challenge, [ 42 ] as the incorporation of electroactive fillers into printable resins can dramatically impact the rate of photopolymerization or clog the printing nozzle due to particle aggregation during the printing process—arising from poor particle dispersibility. [ 50 ] Alternatively, 3D printed insulating hydrogels can be endowed with electrical conductivity through 1) soaking the part in monomer solution, and 2) subsequently polymerizing the monomer in situ to generate a double network hydrogel—however such systems have limited control of the final CP loading, and can lack homogenous distribution of incorporated CP.…”
Section: Resultsmentioning
confidence: 99%
“…At 1 wt% loading of ncrys-PEDOT 20 , each of the tested gels demonstrates substantially less modulus reinforcement than what is seen on average with CNTs (130%) or reduced graphene oxide (170%). [5] Recent work with hydrophilic CPs has suggested that hygroscopic side chains can reduce modulus reinforcement; [42,43] the internal PSS surfactant may behave similarly, preventing detrimental stiffening upon loading. As the impact of ncrys-PEDOT X on stiffness is hydrogel dependent, future application of the particles should also investigate reinforcement behavior.…”
Section: Conductive Ncrys-pedot X Incorporated Hydrogelsmentioning
confidence: 99%
“…Following the printing, the hybrid CSS is fabricated by injecting the hydrogel-GO precursor solution into the structure and gelling it at 37°C. The combination of 3D printing technology (20,21) and the injectable thermoresponsive hydrogel (23,25) allows for the convenient and swift fabrication of a customizable soft-rigid hybrid system. The methacrylated poly(1,8-octanediol-citrate) (mPOC) was used as a 3D printable polymer and developed from POC via two steps (Fig.…”
Section: Gp Hydrogel Integrates Into P-ha Enabling Css Fabricationmentioning
confidence: 99%
“…CSS should not only provide a microenvironment conducive to osteogenesis but also conform to the defect geometry in 3D for effective integration and function recovery ( 19 ). Additive manufacturing using continuous liquid interface production (CLIP) offers advantages in printing speed and complex architecture fabrication at high resolutions ( 20, 21 ). Therefore, 3D-printed CSS developed using CLIP technology has significant potential in bone reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] For that reason, additive manufacturing 3D printing methods are increasingly being used in order to create conductive hydrogels using different type of techniques such as inkjet printing, [17,18] extrusion-based printing [19][20][21] and light-based printing. [22][23][24] Very recently, we have shown that PEDOT can be copolymerized with poly(𝜖-caprolactone) (PCL) biopolyester, leading to PEDOT-g-PCL graft copolymers. This copolymer shows excellent shear-thinning behavior to be processed by extrusion-based printing in order to synthetize 3D scaffolds to induce muscle cells (myotubes) differentiation.…”
Section: Introductionmentioning
confidence: 99%